Behavioral Problems Reported by Adolescents and Parents from HIV Affected Families in China. - Li, Li; Comulada, W. Scott; Lan, Chiao-Wen; Lin, Chunqing; Xiao, Yongkang; Ji, Guoping (Journal of Child & Family Studies, 2018)
This study examined the influence of various factors on the behavioral problems of adolescents affected by HIV while considering the agreement between adolescent and parent reports on problem behaviors. A total of 136 families each with one parent living with HIV (PLH) and one child aged 13–18 were included. Structural equation modeling was used to explore relationships between selected family measures and adolescent’s problem behaviors. The correlation between the PLH and adolescent-reported behavioral problem measures was low (β = 0.11). PLH-reported adolescent problem behaviors were negatively related to PLH-reported parental bonding (β = −0.39), family routines (β = −0.26), and positively associated with family conflict (β = 0.21). Adolescent-reported family participation was associated with self-reported problem behaviors (β = −0.35). Our study reported discrete perceptions of adolescent problem behaviors from parents’ and adolescents’ points of view. Future intervention efforts should emphasize family contextual factors to improve behavioral outcomes in adolescents affected by HIV.